OSMOTIC LAXATIVES IN TREATMENT OF CHRONIC CONSTIPATIONS IN CHILDREN - E. A. Kornienko; K. M. Komarov; M. Yu. Tipikina; T. B. Loboda (Вопросы современной педиатрии, 2012)
A comparative trial including 80 patients at the age of 1–16 years old was performed in order to evaluate efficacy and safety of osmotic laxatives polyethylene glycol with molecular mass of 4000 kDa and lactulose (46 children received polyethylene glycol, 34 — lactulose) in children with chronic functional constipations. The observation period during the treatment lasted for 2 weeks, clinical and laboratory evaluation of the therapy efficacy and safety was carried out. The normalization of stool was achieved on the average in 3 days of treatment in both groups, pain and dyspepsia were arrested in the majority of the patients. Stool consistency was normalized. No side-effects were registered. However in the first days of lactulose treatment there were reliably more complaints on flatulence and rumbling, which passed spontaneously. Lactulose and polyethylene glycol were shown to be effective and safe in treatment of chronic functional constipations in children and can be recommended for usage even in infants.Keywords: children, constipations, lactulose.